2007
DOI: 10.1111/j.1440-1746.2006.04612.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin‐18 in the development of acute pulmonary injury induced by intestinal ischemia/reperfusion and its possible mechanism

Abstract: These data suggested a role of IL-18 in the activation and sequestration of neutrophils in lungs. Our results were consistent with the hypothesis that increased sequestration of neutrophils and microvascular leakage might, respectively, relate to the increased IL-18 level and the elevation of TNF-alpha/iNOS activity, and these two aspects might synergically contribute to intestinal I/R-induced pulmonary dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
10

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 31 publications
0
14
0
10
Order By: Relevance
“…PCR was performed using Taq 5X Master Mix (New England Biolabs) and the following primers obtained from Integrated DNA Technologies (Coraville, Iowa): IL-1␤ 5 -CAACCAACAAGTGATATTCTCCATG-3 , 5 -GATCCACACTCTCCAGCTGCA-3 (Sugama et al 2007); IL-6 5 -CCTCTCTGCAAGAGACTTCC-3 , 5 -GCACAACTCTTTTCTCATTTCC-3 (He et al 2006), TNF-␣ 5 -CAGGGGCCACCACGCTCTTC-3 , 5 -TGACCTCAGCGCTGAGTTGGT-3 (Yang et al 2007); iNOS 5 -CCTTGTTCAGCTACGCCTTC-3 , 5 -AAGGCCAAACACAGCATACC-3 (Kyuhou et al 2006); SOCS-1 5 -CAGGTGGCAGCCGACAATGCGATC-3 , 5 -CGTAGTGCTCCAGCAGCTCGAAAA-3 (Liu et al 2010); SOCS-2 5 -GACCAGCTGTCTGGGACGTGTTGA-3 , 5 -GAGAGAGA-AATACTTATACCTGGAAT-3 (Egwuagu et al 2002); SOCS-3 5 -TGCGCCATGGTCACCCACAGCAAGTTT-3 , 5 -GCTCCTTAAAGTGG-AGCATCATACTGA-3 (Egwuagu et al 2002), and 18S rRNA 5 -AAACGGCTACCACATCCAAG-3, 5 -CCTCCAATGGATCCTCGTTA-3.…”
Section: Reverse Transcriptase (Rt)-pcrmentioning
confidence: 99%
“…PCR was performed using Taq 5X Master Mix (New England Biolabs) and the following primers obtained from Integrated DNA Technologies (Coraville, Iowa): IL-1␤ 5 -CAACCAACAAGTGATATTCTCCATG-3 , 5 -GATCCACACTCTCCAGCTGCA-3 (Sugama et al 2007); IL-6 5 -CCTCTCTGCAAGAGACTTCC-3 , 5 -GCACAACTCTTTTCTCATTTCC-3 (He et al 2006), TNF-␣ 5 -CAGGGGCCACCACGCTCTTC-3 , 5 -TGACCTCAGCGCTGAGTTGGT-3 (Yang et al 2007); iNOS 5 -CCTTGTTCAGCTACGCCTTC-3 , 5 -AAGGCCAAACACAGCATACC-3 (Kyuhou et al 2006); SOCS-1 5 -CAGGTGGCAGCCGACAATGCGATC-3 , 5 -CGTAGTGCTCCAGCAGCTCGAAAA-3 (Liu et al 2010); SOCS-2 5 -GACCAGCTGTCTGGGACGTGTTGA-3 , 5 -GAGAGAGA-AATACTTATACCTGGAAT-3 (Egwuagu et al 2002); SOCS-3 5 -TGCGCCATGGTCACCCACAGCAAGTTT-3 , 5 -GCTCCTTAAAGTGG-AGCATCATACTGA-3 (Egwuagu et al 2002), and 18S rRNA 5 -AAACGGCTACCACATCCAAG-3, 5 -CCTCCAATGGATCCTCGTTA-3.…”
Section: Reverse Transcriptase (Rt)-pcrmentioning
confidence: 99%
“…A number of cell types have been reported to produce IL-18, including monocytes and macrophages, epithelial cells, astrocytes, and microglia (11,17,20,50). Similar to IL-1␤, IL-18 may be released under conditions of physiological stress, and increased plasma levels, which may be found in patients with infection, correlate with disease severity (18,31,63). Because of its described proinflammatory effects, IL-18 may act as a bridging molecule that coordinates both innate and adaptive immunity to more effectively respond to invasive infection and inflammation (21,31,41,62).…”
mentioning
confidence: 99%
“…A number of experimental studies have shown that intravenous injection of an anti-mouse IL-18 neutralizing antibody 30 to 60 min prior to ischemia decreased NF-κB and AP-1 activation, serum levels of pro-inflammatory TNF-α, suppression of anti-inflammatory IL-4 and IL-10, CXC chemokine expression, neutrophil infiltration, pulmonary extravasation of Evans Blue dye, apoptosis, and hepatic, pulmonary and myocardial infarct size at 3-24 hours following reperfusion in mouse models of ischemia/reperfusion injury (Takeuchi et al, 2004;Venkatachalam et al, 2009;Yang et al, 2007b). Similarly experimental studies have shown that intravenous or intramyocardial injection of exogenous IL-18 binding protein or mesenchymal stem cells overexpressing IL-18 binding protein, a naturally occurring inhibitor, selectively neutralized IL-18, and decreased expression of proinflammatory mediators (TNF-α, IL-1β, IL-6, IL-18, MCP-1 and ICAM-1), macrophage infiltration, renal tubule epithelium apoptosis, infarct size and increased vascular endothelial growth factor (VEGF) expression, proliferation of renal tubule epithelium and leftventricular ejection fraction at 6-72 hours after reperfusion in rat models of renal ischemia/reperfusion injury and myocardial infarction (Wang et al, 2009;Wang et al, 2012a).…”
Section: Targeting Secondary Messengers: Ros Pkr and β-Arrestin-2mentioning
confidence: 99%